The Functional Independence Measure 18-item version can be reported as a unidimensional interval-scaled metric: Internal construct validity revisited - Roxanne Maritz; Alan Tennant; Carolina Fellinghauer; Gerold Stucki; Birgit Prodinger (Medical Journals Sweden, 2019)
Objective: Since the 1990s the Functional Independence Measure (FIM™) was believed to measure 2 different constructs, represented by its motor and cognitive subscales. The practice of reporting FIM™ total scores, together with recent developments in the understanding of the influence of locally dependent items on fit to the Rasch model, raises the question of whether the FIM™ 18-item version can be reported as a unidimensional interval-scaled metric. Design: Rasch analysis of the FIM™ using testlet approaches to accommodate local response dependency. Patients: A calibration sample containing 946 cases of data from 11,103 patients undergoing neurological or musculoskeletal rehabilitation in Switzerland in 2016. Results: Baseline analysis and the traditional testlet approach showed no fit with the Rasch model. When items were grouped into 2 testlets, fit to the Rasch model was achieved, indicating unidimensionality across all 18 items. A transformation table to convert FIM™ raw ordinal scores to the corresponding Rasch interval scaled values was created. Conclusion: This study provides evidence that FIM™ total scores represent a unidimensional set of items, supporting their use in clinical practice and outcome reporting when applying the respective transformation table. This provides a basis for standardized reporting of functioning.